2008
DOI: 10.1177/0885066608321389
|View full text |Cite
|
Sign up to set email alerts
|

Use of Sildenafil to Facilitate Weaning From Inhaled Nitric Oxide in Children With Pulmonary Hypertension Following Surgery for Congenital Heart Disease

Abstract: Pulmonary hypertension frequently complicates the postoperative management of patients after congenital cardiac surgery. Inhaled nitric oxide is an effective treatment option, but rebound pulmonary hypertension can occur upon its withdrawal. Sildenafil may facilitate its withdrawal by restoring cyclic guanosine monophosphate availability via phosphodiesterase-5 inhibition. The purpose of this study was to evaluate the use of sildenafil in facilitating weaning from inhaled nitric oxide after congenital cardiac … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(58 citation statements)
references
References 24 publications
2
48
0
6
Order By: Relevance
“…Treatment with sildenafil significantly reduced iNO requirements within 24 h and facilitated iNO weaning for all seven patients [49]. Case reports describe similar observations [4,5,56,70].…”
Section: Inhaled Nitric Oxide Weaningsupporting
confidence: 64%
See 2 more Smart Citations
“…Treatment with sildenafil significantly reduced iNO requirements within 24 h and facilitated iNO weaning for all seven patients [49]. Case reports describe similar observations [4,5,56,70].…”
Section: Inhaled Nitric Oxide Weaningsupporting
confidence: 64%
“…Rebound PHTN, presenting as an acute increase in PAP and cardiopulmonary instability, can complicate the withdrawal of iNO. Two small studies [49,58] in addition to several case reports [4,5,42,70] have identified sildenafil as a means for minimizing rebound PHTN and the need for prolonged iNO therapy. Namachivayam et al [58] demonstrated sildenafil's efficacy to facilitate iNO weaning of 29 infants and children.…”
Section: Inhaled Nitric Oxide Weaningmentioning
confidence: 99%
See 1 more Smart Citation
“…21,22 In pediatric patients who failed to be weaned from iNO after surgery for congenital heart disease, sildenafil has been shown to facilitate weaning. 23 Our first step toward obtaining CTICU staff buy-in for iNO initiation and weaning guidelines was review of the patients and iNO usage from the previous year. The inconsistent initiation and weaning (or not weaning) was obvious.…”
Section: Discussionmentioning
confidence: 99%
“…Sildenafil serum levels peak at 1-2 h after oral dose, which is important to know to monitor for adverse effects such as hypotension, flushing, nasal congestion, priapism and agitation. Sildenafil is particularly beneficial in post-operative patients in preventing rebound PH at the time of iNO withdrawal [141][142][143][144][145].…”
Section: Phosphodiesterase 5 (Pde5) Inhibitorsmentioning
confidence: 99%